2022
DOI: 10.3389/fclim.2022.1014138
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and characteristics of the Indo-western Pacific Ocean capacitor

Abstract: Coherently coupled ocean-atmosphere variability of the tropical Indo-Pacific Oceans gives rise to the predictability of Asian summer climate. Recent advances in Indo-western Pacific Ocean capacitor (IPOC) theory and the relationship with El Niño-Southern Oscillation (ENSO) are reviewed. The IPOC features tropical Indian Ocean (TIO) warming and an anomalous anticyclonic circulation over the western North Pacific (WNPAAC), the latter driving water vapor transport to East Asia and causing extreme events, e.g., he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 166 publications
2
1
0
Order By: Relevance
“…Both local wind forcing and oceanic Rossby waves exert substantial influence on the phytoplankton size structure in the central southern TIO from the development to the maturity of the IOD events. Previous studies found that downwelling oceanic Rossby waves associated with the anomalous anticyclonic wind stress curls in the southeast TIO deepen the thermocline and warm the subsurface in the southwestern TIO [35]. Our study also revealed that Rossby waves persisted in modulating the variations in phytoplankton size structure during IOD events.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Both local wind forcing and oceanic Rossby waves exert substantial influence on the phytoplankton size structure in the central southern TIO from the development to the maturity of the IOD events. Previous studies found that downwelling oceanic Rossby waves associated with the anomalous anticyclonic wind stress curls in the southeast TIO deepen the thermocline and warm the subsurface in the southwestern TIO [35]. Our study also revealed that Rossby waves persisted in modulating the variations in phytoplankton size structure during IOD events.…”
Section: Discussionsupporting
confidence: 75%
“…Figure 5 presents longitude-tim sections of the CSD slope anomalies for the three strong positive and three strong nega tive IOD events. The IOD exhibits seasonal phase-locking characteristics, developin from late spring to early summer, strengthening in summer, peaking in autumn, an gradually diminishing in winter [35]. The variations in CSD slope anomalies in th southeastern TIO were generally consistent with the evolution process of the IOD (Fig ure 5).…”
Section: Features In Iod Eventssupporting
confidence: 56%
See 1 more Smart Citation